Effects of pH on Adsorption of Remazol Turquoise Blue Dyez on MgO/TiO2 Nanocomposite - Rizka Novembrianto; Ya-Fen Wang; Sheng-Jie You; Restu Hikmah Ayu Murti; Muhammad Abdus Salam Jawwad (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
A magnesium oxide and titanium (II) oxide nanocomposite, MgO/TiO2 was synthesized to improve its surface area thus its adsorption capability may be risen. The synthesis was applying sol-gel method, combining MgO and TiO2 nanoparticles with NaOH becomes a nanocomposite with higher surface area. The pH effect on adsorption were analyzed. The expectation of using MgO/TiO2 compared with TiO2 and MgO alone is it may react faster on an adsorption trial with remazol turquoise blue dye, and the TiO2 may give its photocatalysis ability to the synthesized material. Less acid the condition of the solution, the capability of the MgO/TiO2 catalyst on adsorbing the remazol turquoise blue dye will increasing. After 90 minutes, the photocatalysis rate surpass the adsorption rate and reach equilibrium.